A integração de alunos de escolas particulares de São Paulo: a pertença ao grupo - Minga, Maria de Jesus Pereira Amaral (2002)
The initial goal of this essay was to investigate the trouble in human being s adaptation to the shifts which took place in their lives, in particular to verify the adaptation of those pupils who were transferred among private schools. In starting the survey I realized that the bibliography is slim and presents inconsistent concepts and that my object was not the adaptation but the belonging to a group. Thus I researched the group belonging of pupils from the 5th grade to the 8th grade transferred among private schools in São Paulo county. The essay, regarding its steps, combined a bibliographic survey, focusing the theoric grounding concerning the group belonging and a field work which was caracterized by a case study, with a qualitative methodological target regarding the object of the study. With this survey modality, through semi structured interviews, it was possible to seize the reality, to captivate the relations and verify in the school routine, how the group belonging is made. I carried out this investigation in a São Paulo county s private school where I interviewed seventeen pupils from the 5th to the 8th grade from morning and afternoon sessions and also three educacional guides. The achieved outcomes contributed to testify the necessity such schools have to work with the group belonging close to those pupils who were received by them. This work is composed of three chapters. The 1st chapter deals with the group belonging, with basics in Pichon-Rivière; the 2nd chapter focuses the adolescence and the 3rd one approaches how the question concerning the group belonging is dealt with in a São Paulo county s school. With this study I intend to contribute to the knowledge production perspective, as well as the performance regarding the professionals wrapped with the question.